Instrumental variables estimation for nonparametric models - Whitney K. Newey; James Powell (Centre for Microdata Methods and Practice (cemmap), 2017)
Whitney Newey and James Powell, founding CeMMAP Fellows, wrote an influential paper on instrumental variable estimation of an additive error non-parametrically specified structural equation, presented at the December 1988 North American Winter Meetings of the Econometric Society. A version circulated in 1989 but the results were not published until 14 years later: "Instrumental Variable Estimation of Nonparametric Models", Econometrica, 71(5), (September 2003), 1565-1578. The 1989 working paper is often referred to, but hard to find. For the sake of completeness CeMMAP is pleased to publish the 1989 paper.
Keywords: 330